\( 1 \leftarrow \) For \( f(x)=1-x \) and \( g(x)=2 x^{2}+x+2 \), find the following functions. a. \( (f \circ g)(x) ; b .(g \circ f)(x) ; \) c. \( (f \circ g)(3) ; \) d. \( (g \circ f)(3) \) a. \( (f \circ g)(x)=\square \) (Simplify your answer.)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To find \( (f \circ g)(x) \), we will substitute \( g(x) \) into \( f(x) \). Given: - \( f(x) = 1 - x \) - \( g(x) = 2x^{2} + x + 2 \) We have: \[ (f \circ g)(x) = f(g(x)) = f(2x^{2} + x + 2) \] Now, substitute \( g(x) \) into \( f(x) \): \[ f(2x^{2} + x + 2) = 1 - (2x^{2} + x + 2) \] This simplifies to: \[ = 1 - 2x^{2} - x - 2 \] \[ = -2x^{2} - x - 1 \] Thus, a. \( (f \circ g)(x) = -2x^{2} - x - 1 \) Now for part b, \( (g \circ f)(x) \): We need to substitute \( f(x) \) into \( g(x) \): \[ (g \circ f)(x) = g(f(x)) = g(1 - x) \] Now substitute \( f(x) \) into \( g(x) \): \[ g(1 - x) = 2(1 - x)^{2} + (1 - x) + 2 \] Calculating \( (1 - x)^{2} = 1 - 2x + x^{2} \): \[ = 2(1 - 2x + x^{2}) + 1 - x + 2 \] Distributing the 2: \[ = 2 - 4x + 2x^{2} + 1 - x + 2 \] Combining like terms: \[ = 2x^{2} - 5x + 5 \] Thus, b. \( (g \circ f)(x) = 2x^{2} - 5x + 5 \) Next, for part c, we calculate \( (f \circ g)(3) \): \[ (f \circ g)(3) = -2(3)^{2} - (3) - 1 \] \[ = -2(9) - 3 - 1 \] \[ = -18 - 3 - 1 \] \[ = -22 \] So, c. \( (f \circ g)(3) = -22 \) Finally, for part d, \( (g \circ f)(3) \): \[ (g \circ f)(3) = 2(3)^{2} - 5(3) + 5 \] \[ = 2(9) - 15 + 5 \] \[ = 18 - 15 + 5 \] \[ = 8 \] Therefore, d. \( (g \circ f)(3) = 8 \)